KEANEKARAGAMAN JENIS REPTIL DI KAWASAN HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR - Nur Fitriana; Defri Yoza; Yossi Oktorini (JURNAL ILMU-ILMU KEHUTANAN, 2017)
Rumbio village in Kampar district Kampar regency Riau province began to be recognized by local and foreign communities due to the existence of the Forest Reserve. The Forest Reserve of Kenegerian Rumbio it stored a variety of natural resources as well as the flora and fauna typical to this area.One of the richness of the fauna in the Rumbio cutomary prohibition forest are reptiles that need preservation to avoid extinction. Research on reptile diversity is one of the efforts to preserve the existence of reptiles. The purpose of this research is to identify the types of reptiles found in Rumbio customary prohibition forest,reptile diversity known by using of Visual Encounter Survey (VES) method and Passive sampling. The results showed that the reptile species found were 116 individuals from 10 species and 5 families. Families that found such as Gekkonidae, Geomydidne, Homalopsis buccata, Colubridae, Scincidae.